Modified extrusion-spheronization as a technique of microencapsulation for stabilization of choline bitartrate using hydrogenated soya bean oil - Gangurde, Avinash Bhaskar (Int J Pharm Investig, 2015)
INTRODUCTION: Choline bitartrate (CBT) is a vital nutrient for fetal brain development and memory function. It is hygroscopic in nature which is associated with stability related problem during storage such as development of fishy odor and discoloration. AIM: Microencapsulation method was adopted to resolve the stability problem and for this hydrogenated soya bean oil (HSO) was used as encapsulating agent. MATERIALS AND METHODS: Industrially feasible modified extrusion-spheronization technique was selected for microencapsulation. HSO was used as encapsulating agent, hydroxypropyl methyl cellulose E5/E15 as binder and microcrystalline cellulose as spheronization aid. Formulated pellets were evaluated for parameters such as flow property, morphological characteristics, hardness-friability index (HFI), drug content, encapsulation efficiency, and in vitro drug release. The optimized formulations were also characterized for particle size (by laser diffractometry), differential scanning calorimetry, powder X-ray diffractometry (PXRD), Fourier transform infrared spectroscopy, and scanning electron microscopy. RESULTS AND DISCUSSIONS: The results from the study showed that coating of 90% and 60% CBT was successful with respect to all desired evaluation parameters. Optimized formulation was kept for 6 months stability study as per ICH guidelines, and there was no change in color, moisture content, drug content, and no fishy odor was observed. CONCLUSION: Microencapsulated pellets of CBT using HSO as encapsulating agent were developed using modified extrusion spheronization technique. Optimized formulations, CBT 90% (F5), and CBT 60% (F10), were found to be stable for 4M and 6M, respectively, at accelerated conditions.